The Dynamics of Early Islamic Thought: Conceptions and Differences of the Hanafi, Maliki, Shafi’i, and Hanbali Mazhab - Sofian Sofian; Nurul Alvi Chindi Fadhilah; Muhammad Firdaus; M. Yakub (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study examines the dynamics of early Islamic thought that underlie the emergence of the four major mazhabs of jurisprudence, namely Hanafi, Maliki, Shafi'i, and Hanbali. After the Prophet Muhammad SAW passed away, Muslims faced challenges in the form of territorial expansion and social complexity, which triggered differences in legal interpretation. Using a library research method with descriptive-qualitative analysis, this study explores the socio-political background, ijtihad methodology (ushul fiqh), as well as the characteristics of each mazhab. The results of the study show that differences of opinion among the mazhab imams are not a form of division, but rather a dynamic intellectual response to the realities of the time. The Hanafi mazhab is known for its rationalist approach (ahl al-ra’y), the Maliki mazhab strongly adheres to the traditions of the people of Medina (amal ahl al-Madinah), the Shafi'i mazhab successfully synergizes text and reason systematically, while the Hanbali mazhab tends to be textual and conservative. This study emphasizes that the diversity of these methodologies constitutes an intellectual wealth that preserves the flexibility of Islamic law in addressing various contemporary issues, ranging from transactional matters to practical worship.